A–D–A'–D–A type nonfused ring electron acceptors for efficient organic solar cells via synergistic molecular packing and orientation control - Wenkui Wei; Xia Zhou; Shuting Pang; Jiadong Zhou; Xiyue Yuan; Junyu Li; Yuting Chen; Langheng Pan; Zengqi Xie; Hongbin Wu; Fei Huang; Yong Cao; et al. (Aggregate, 2024)
Abstract Nonfused ring electron acceptors (NFREAs) are promising candidates for future commercialization of organic solar cells (OSCs) due to their simple synthesis. Still, the power conversion efficiencies (PCEs) of NFREA‐based OSCs have large room for improvement. In this work, by merging end group halogenation and side chain engineering, we developed four A–D–A'–D–A type NFREAs, which we refer to as EH‐4F, C4‐4F, EH‐4Cl, and C4‐4Cl. Single crystal X‐ray diffraction revealed that multiple intermolecular S···F interactions between cyclopentadithiophene and 5,6‐difluoro‐3‐(dicyanomethylene)indanone could cause an unfavorable dimer formation, leading to ineffective π–π stackings in EH‐4F and C4‐4F, whereas no such dimer was found in EH‐4Cl and C4‐4Cl after replacing with 5,6‐dichloro‐3‐(dicyanomethylene)indanone. Moreover, although the shorter n‐butyl side chain resulted in a closer molecular packing in C4‐4Cl, EH‐4Cl (2‐ethylhexyl substitution) with proper crystallinity exhibited enhanced face‐on orientation in thin film, which is favorable for vertical charge transport and further reducing charge recombination. As a result, a PCE of 13.0% is obtained for EH‐4Cl‐based OSC with a fill factor of 0.70. This work highlights the importance of molecular packing and orientation control toward future high‐performance A–D–A'–D–A type NFREAs.